Effect of obesity on functional outcomes at 6 months post-stroke among elderly Koreans: a prospective multicentre study. Issue 12 (18th December 2015) - Jang, Shin Yi; Shin, Yong-Il; Kim, Deog Young; Sohn, Min Kyun; Lee, Jongmin; Lee, Sam-Gyu; Oh, Gyung-Jae; Lee, Yang-Soo; Joo, Min Cheol; Han, Eun Young; Chang, Won Hyuk; Kang, Chung; et al.
Abstract : Objectives: We examined whether obesity based on body mass index (BMI) was a predictor of functional independence measure (FIM) at 6 months after ischaemic stroke onset while adjusting for stroke risk factors and covariates and stratifying by age group. Design: This is an interim report of the Korean Stroke Cohort for Functioning and Rehabilitation that was designed as a nested case study within a nationwide hospital-based cohort. Setting: We identified all patients who were admitted to nine representative hospitals in Korea from 2012 until 2014 under a diagnosis of acute first-ever ischaemic stroke. The hospitals were selected from the metropolitan district, mid-sized cities and a small-sized city. Participants: The sample included 2057 patients with acute ischaemic stroke who were at least 18 years old. Primary and secondary outcome measures: We divided participants into two age levels (<65 and ≥65 years). Participants were classified into five groups according to their baseline BMI at admission: underweight (BMI<18.5), normal (18.5≤BMI<23), overweight (23≤BMI<25), obese (25≤BMI<30) and extremely obese (30≤BMI). Results: The proportion of patients who were aged ≥65 years was 55.0%. The proportions of underweight, normal, overweight, obese and extremely obese patients were 2.6%, 24.3%, 29.6%, 37.2% and 6.3%, respectively, in the <65 years group and 5.5%, 34.5%, 27.9%, 28.8% and 3.3%, respectively, in the ≥65 years group. In a multiple linear regression, the 6-month FIM after stroke in the elderly group was significantly associated with being extremely obese (7.95, p<0.05) after adjusting for confounding variables. In the <65 years group, the 6-month FIM was not associated with any weight category. Conclusions: This nationwide hospital-based cohort study showed that extreme obesity is a predictor of a good 6-month FIM, especially in patients with ischaemic stroke who are at least 65 years of age.